Pengalaman Siswa Madrasah Ibtidaiyah Dalam Menghadapi Kecemasan Akademik: Perspektif Psikologi Pendidikan Islam - Nurmaghfiroh, Ariyani; Shanie, Arsan; Musyarofah, Nurul; Sudardi, Zahra Adenia; Ulia, Rizka Faridatul; Hidayah, Lailatul (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to explore the experiences of Madrasah Ibtidaiyah (MI) students in dealing with academic anxiety and to understand this phenomenon through the lens of Islamic educational psychology. Academic anxiety among elementary-level students is often overlooked, despite its significant impact on their emotional and spiritual development. This research employs a qualitative phenomenological approach, using in-depth interviews with students and teachers. The findings reveal that academic anxiety manifests through both physical and emotional symptoms such as trembling, insomnia, stage fright, and low self-esteem. The contributing factors include parental and teacher pressure, social environment, academic difficulties, and lack of self-confidence. Students rely heavily on religious coping strategies such as prayer, remembrance (dhikr), and recalling parental advice. The Islamic educational psychology perspective emphasizes the importance of values like tawhid, trust in God (tawakkul), patience (sabr), and positive thinking (husnudzon) in building psychological resilience. The study highlights the need to integrate spiritual approaches into the madrasah education system to foster a peaceful learning environment and promote students' mental well-being.